Smart Warning System Prototype DAM - Barelvi, Ahmad; Basri, Mhd (Ilmu Bersama Center, 2025)
This study designs a flood detection prototype by measuring water flow speed and water level using a flowmeter sensor, water level sensor, buzzer as a warning device, and ESP32 microcontroller as the controller. The research was conducted through a literature review, collecting data from journals, online articles, and statistics related to sensor technology and ESP32. This research aims to design, develop and test a prototype of an integrated smart early warning system for risk management and mitigation in dam areas. The system is designed to be able to detect potential hazards in real-time, such as sudden increases in water volume, extreme rainfall, potential landslides on dam slopes, or structural damage. Testing ensured that all components functioned as expected, with results demonstrating reliable system performance. This IoT prototype successfully monitored dam parameters in real- time, with an average delay of 42 ms, 84.3 ms, and 73.8 ms, no data packet loss (0%), and stable throughput at 92.6 Kbps, 83.8 Kbps, and 86.2 Kbps.